A 1D palladium coordination polymer and its catalytic activity in microwave-assisted Sonogashira reactions. (1st July 2021) - Lee, Gang Min; Lee, Soon W.
Graphical abstract: Abstract: A palladium coordination polymer, [Pd(dppp)(L)](OTf)2 ·(H2 O)] (1 ) (dppp = 1, 3-bis(diphenylphosphino)propane), was prepared from a bipyridine-type ligand (L = (4-py)–CH = N–C10 H6 –N = CH–(4-py)) and [Pd(dppp)](OTf)2 . An X-ray diffraction study showed that it has a one-dimensional zigzag chain structure and the triflate ions act as counterions. Compound 1 exhibited Sonogashira coupling reactivity in air under microwave conditions.